The effect of health insurance and socioeconomic status on women’s choice in birth attendant and place of delivery across regions in Indonesia: a multinomial logit analysis - Barbara McPake; John Tayu Lee; Tiara Marthias; Kanya Anindya; Likke Prawidya Putri; Diah Ayu Puspandari (BMJ Global Health, 2023)
Background Evidence suggests that women gave birth in diverse types of health facilities and were assisted by various types of health providers. This study examines how these choices are influenced by the Indonesia national health insurance programme (Jaminan Kesehatan Nasional (JKN)), which aimed to provide equitable access to health services, including maternal health.Methods Using multinomial logit regression models, we examined patterns and determinants of women’s choice for childbirth, focusing on health insurance coverage, geographical location and socioeconomic disparities. We used the 2018 nationally representative household survey dataset consisting of 41 460 women (15–49 years) with a recent live birth.Results JKN coverage was associated with increased use of higher-level health providers and facilities and reduced the likelihood of deliveries at primary health facilities and attendance by midwives/nurses. Women with JKN coverage were 13.1% and 17.0% (p<0.05) more likely to be attended by OBGYN/general practitioner (GP) and to deliver at hospitals, respectively, compared with uninsured women. We found notable synergistic effects of insurance status, place of residence and economic status on women’s choice of type of birth attendant and place of delivery. Insured women living in Java–Bali and in the richest wealth quintile were 6.4 times more likely to be attended by OBGYN/GP and 4.2 times more likely to deliver at a hospital compared with those without health insurance, living in Eastern Indonesia, and in the poorest income quantile.Conclusion There are large variations in the choice of birth attendant and place of delivery by population groups in Indonesia. Evaluation of health systems reform initiatives, including the JKN programme and the primary healthcare strengthening, is essential to determine their impact on disparities in maternal health services.